Body Composition in Type 2 Diabetes: Change in Quality and not Just Quantity that Matters - Solanki, Jayesh D. (Int J Prev Med, 2015)
BACKGROUND: Deranged body fat and muscle mass are aftermaths of uncontrolled diabetes. Anthropometric methods like body mass index (BMI) do not give qualitative inferences like total body fat (TBF), visceral fat (VF) or subcutaneous fat (SF) that can be given by bio-electrical impedance analysis (BIA). We studied body composition of type 2 diabetics in comparison to controls matched by age-sex, weight and BMI separately. METHODS: Seventy-eight under-treatment type 2 diabetics of either sex with known glycemic and lipidemic control and equal number of controls with three patterns of matching were taken from our city. We derived parameters of body composition in both groups by Omron Karada Scan (Model HBF-510, China), using the principle of tetra poplar BIA and compared them for statistical significance. RESULTS: We found significantly more SF (30.47% ± 7.73%), VF (11.94% ± 4.97%) and TBF (33.96% ± 6.07%) and significantly lesser skeletal muscle mass (23.39% ± 4.49%) in type 2 diabetics as compared to controls, persisting even after matching with weight or BMI. On assessing qualitatively, the risk of high VF, high TBF, low skeletal muscle mass was significantly high in type 2 diabetics, which were 10.41, 3.01, 9.21 respectively for comparable BMI and 6.78, 3.51, 11.93 respectively for comparable weight. CONCLUSIONS: BIA reveals that type 2 diabetics have more ectopic fat on the expense of skeletal muscle that persists even after matching by weight or BMI, both quantitatively and qualitatively. Measurement of body composition can be included as a primary care strategy to motivate lifestyle modifications while managing metabolic derangements of type 2 diabetes.